Ultrasonic-induced excess vacancies in friction stir processing and exploration of acoustoplastic effect. (August 2020) - Hu, Yanying; Liu, Huijie; Fujii, Hidetoshi; Araki, Hideki; Sugita, Kazuki; Liu, Ke
Abstract: The interactions of vacancy with dislocations and precipitates in the ultrasonic affected friction stir processing were investigated using positron annihilation spectroscopy, transmission electron microscopy and molecular dynamics simulation. Excess vacancies were induced by the ultrasonic via reducing the vacancy formation energy, resulting in a reduced Peierls stress and a concurrent enhancement of dislocation climb, contributing to the acoustic softening. In the cooling stage, appreciable helical dislocations were formed due to the quick condensations of vacancies on screw dislocations, leading to the residual hardening. Graphical abstract: Image, graphical abstract